Finite time blow-up for a class of parabolic or pseudo-parabolic equations - Sun, F.; Liu, Lishan; Wu, Yong Hong (Pergamon Press, 2018)
In this paper, we study the initial boundary value problem for a class of parabolic or pseudo-parabolic equations: